Metabolic tumor burden: A new promising way to reach precise personalized therapy in PDAC. Issue 2 (10th April 2015) - Xiang, Jinfeng; Liu, Liang; Wang, Wenquan; Xu, Huaxiang; Wu, Chuntao; Xu, Jin; Liu, Chen; Long, Jiang; Ni, Quanxing; Yu, Xianjun
Highlights: The treatment for pancreatic ductal adenocarcinoma (PDAC) is still in an austere predicament. People concentrate on screening effective factors to instruct a precise treatment. The conventional methods are always based on CT or serum tumor marker levels, which have limited merits. The authors introduce a new perspective for the pretreatment evaluation of PDAC based on cancer metabolism. Metabolic tumor burden may potentially serve as a new promising approach to reach precise personalized therapy in PDAC. Abstract: Pancreatic cancer is currently one of the deadliest solid malignancies and pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer. In the past decade, diagnostics and surgical techniques for PDAC have been evolving steadily; however, clinical outcomes of patients with PDAC have shown little, if any, improvement. Subgroup classification based on accurate prediction of prognosis in patients with pancreatic cancer is important for treatment selection and clinical decision-making. The traditional method to evaluate prognosis relies on the TNM staging system, but it may not reflect the true status of every patient due to individual biological differences. Metabolomics is a field of study that involves the identification and quantification of metabolites present in a biological system. Analysis of metabolic differences between cancerous and noncancerous tissues can provide novel insights into tumor biology that are closely associated with disease prognosis and diagnosis. Therefore, evaluation of metabolic tumor burden may improve the accuracy of the clinical decision-making process, thereby facilitating optimization of the treatment strategies for pancreatic cancer.